The new regulatory tools of the 2016 Health Law to fight drug shortages in France. Issue 5 (May 2017) - Bocquet, François; Degrassat-Théas, Albane; Peigné, Jérôme; Paubel, Pascal
Highlights: European health systems are hardly hit by drug shortages since several years. These drug shortages may have a serious impact on public health. In 2012, the French legislator took regulatory action to fight against them. In 2016, France acquired new legal tools to face this critical issue. France now implements coercive measures to take up this public health challenge. Abstract: Drug shortages are becoming worrying for public health in the European Union. The French public authorities first took action against the causes of drug shortages in 2011 with a law, followed by a decree in 2012 to overcome the dysfunctions of the pharmaceutical distribution channel. These texts would establish emergency call centres implemented by pharmaceutical companies for pharmacists and for wholesalers to inform of shortages, and would oblige pharmaceutical companies to inform health authorities of any risk of potential shortage situation; they would also reinforce the declaration regime of the territory served by wholesalers. Through the Health Law of January 2016, France acquired new regulatory tools in order to fight against these shortages and wanted to target the drugs for which they are the most detrimental: the major therapeutic interest (MTI) drugs. Furthermore, this new text reinforces the legal obligations of pharmaceutical companies and of wholesalers for drug shortages and sets out the enforcement of sanctions in case of breach of these obligations. France's goal is ambitious: to implement coercive measures aiming at making the actors of the drug distribution channel aware of their responsibilities in order to take up the public health challenge triggered by drug shortages.